Apical‐root apoplastic acidification affects cell wall extensibility in wheat under salinity stress. Issue 4 (7th September 2021) - Shao, Yang; Feng, Xiaohui; Nakahara, Hiroki; Irshad, Muhammad; Eneji, A. Egrinya; Zheng, Yuanrun; Fujimaki, Haruyuki; An, Ping
Abstract: Plant salt tolerance is associated with a high rate of root growth. Although root growth is governed by cell wall and apoplastic pH, the relationship between these factors in the root elongation zone under salinity stress remains unclear. Herein, we assess apoplastic pH, pH‐ and expansin‐dependent cell wall extensibility, and expansin expression in the root elongation zone of salt‐sensitive (Yongliang‐15) and ‐tolerant (JS‐7) cultivars under salinity stress. A six‐day 80 mM NaCl treatment significantly reduced apical root apoplastic pH in both cultivars. Using a pH‐dependent cell wall extensibility experiment, we found that, under 0 mM NaCl treatment, the optimal pH for cell wall loosening was 6.0 in the salinity‐tolerant cultivar and 4.6 in the salinity‐sensitive cultivar. Under 80 mM treatment, a pH of 5.0 mitigated the cell wall stiffness caused by salinity stress in the salinity‐tolerant cultivar but promoted cell wall stiffening in the salinity‐sensitive cultivar. Salinity stress altered expansin expression and differentially affecting cell wall extensibility under pH 5.0 and 6.0. TaEXPA8 might be relative to cell wall loosening at pH 5.0, whereas TaEXPA5 relative to cell wall loosening at pH 6.0. These results elucidate the relationship between expansins and cell wall extensibility in the root elongation zone, with important implications for enhancing plant growth under salinity stress.